Cervical lymphadenopathy as initial presentation of metastatic prostate cancer: A retrospective study of five cases and literature review - Liu, Yangyang; Dai, Zhihong; Hao, Jiange; Wang, Liang; Liu, Zhiyu (Frontiers in Surgery, 2023)
Cervical lymphadenopathy as the initial presentation of metastatic prostate cancer is particularly uncommon, and easily misdiagnosed. In the current study, we describe five cases of metastatic prostate cancer in our hospital that presented with cervical lymphadenopathy as an initial symptom. The diagnosis was confirmed by needle biopsy of the suspicious lymph nodes and the serum prostate specific antigen (PSA) levels of all patients exceeded 100 ng/ml. The five patients were treated with hormonal therapy; four received traditional hormonal therapy, including bicalutamide and goserelin; one patient received hormonal therapy that included abiraterone and goserelin. Case 1 developed into castration-resistant prostate cancer (CRPC) after 7 months and died after 12 months. Case 2 rejected regular hormonal therapy for personal reasons and died 6 months after the initial diagnosis. Case 3 was still alive at the time of writing. Case 4 was administered with abiraterone, prednisolone and goserelin; the treatment was effective and the patient has remained symptom-free for the last 24 months. Case 5 was treated with hormonal and chemotherapy but died 8 months after diagnosis. In conclusion, any elderly male presenting with cervical lymphadenopathy should be considered the possibility of prostate cancer, especially when the needle biopsy reveals adenocarcinoma. The prognosis for patients presented with cervical lymphadenopathy as the initial presentation is usually poor. Hormone therapy based on abiraterone may yield a better response in such cases.